Vitamin and Carotenoid Intake and Outcomes of In Vitro Fertilization in Women Referring to an Italian Fertility Service: A Cross-Sectional Analysis of a Prospective Cohort Study - Valentina De Cosmi; Sonia Cipriani; Giovanna Esposito; Francesco Fedele; Irene La Vecchia; Giuseppe Trojano; Fabio Parazzini; Edgardo Somigliana; Carlo Agostoni (Antioxidants, 2023)
Background: Nutrition may impact reproductive health and fertility potential. The role of dietary antioxidants in affecting conception and birth outcomes is a topic of emerging interest. Methods: This cross-sectional analysis from a prospective cohort study aims to explore the relationship between the intake of antioxidants, vitamins, and carotenoids and the outcomes of assisted reproduction techniques. Information on the socio-demographic characteristics, health histories, lifestyle habits, and diet information of subfertile couples referred to a fertility center was obtained. Results: A total of 494 women were enrolled. According to the four IVF outcomes considered, 95% of women achieved good quality oocytes, 87% achieved embryo transfer, 32.0% achieved clinical pregnancies, and 24.5% achieved pregnancy at term. Associations were found between age and the number of good quality oocytes (p = 0.02). A moderate level of physical activity in the prior 5 years was associated with a better rate of achieving clinical pregnancy (p = 0.03). Smoking habits, alcohol intake, and caffeine consumption did not show associations with any outcome. No associations were found, even after accounting for potential confounders, with the intake of vitamins C, D, E, and α-carotene, β-carotene, beta-cryptoxanthin, lutein, and folate. Conclusion: Further research is needed to understand how antioxidant intake may have a role in modulating fertility.